Insulin stimulates transport of organic anion compounds mediated by organic anion transporting polypeptide 2B1 in the human intestinal cell line Caco-2. Issue 2 (April 2017) - Kobayashi, Taku; Koizumi, Takahiro; Kobayashi, Masaki; Ogura, Jiro; Horiuchi, Yuichi; Kimura, Yuki; Kondo, Ayuko; Furugen, Ayako; Narumi, Katsuya; Takahashi, Natsuko; Iseki, Ken
Abstract: Organic anion transporting polypeptide 2B1 (OATP2B1) is the major uptake transporter in the intestine, and transports various clinically used therapeutic agents. Insulin acts through the insulin receptor in targeted cells, and Rab8A is one of the insulin signaling pathways. The small intestine in humans also expresses insulin receptor and Rab8A. It has been reported that insulin stimulates peptide transporter 1 (PEPT1) expression at the apical membrane and increases uptake of PEPT1 substrates in small intestine epithelial model cells (Caco-2 cells). However, the effect of insulin on OATP2B1 in the small intestine has not been fully investigated. We found that Rab8A was associated with OATP2B1-mediated estrone-3-sulfate (E3S) uptake. Insulin stimulated the uptake of E3S by Caco-2 cells and the enhancement was sustained for 120 min. The Vmax value of E3S uptake significantly increased upon insulin exposure. Caco-2 cells treated with insulin showed increased OATP2B1 expression at the cell surface. The apical-to-basal transport of E3S was also increased by insulin. The increase of E3S transport was inhibited by the cold condition (4 °C) or the OATP2B1 inhibitor, taurocholate. These results indicate that insulin acts on the small intestine to increase OATP2B1-mediated absorption. Graphical abstract: